Analisis Yuridis Terhadap Alat Bukti Digital dalam Kasus Penganiayaan Mario Dandy - Early Dewati Putri; Taun Taun (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2026)
The absence of clear and unified rules governing digital evidence within Indonesia's general criminal procedural framework creates considerable legal ambiguity, particularly when digital materials are used to prove conventional criminal offenses under the Penal Code. This study aims to examine the legal position of digital evidence in Indonesia's criminal proof system and to analyze its application in the Mario Dandy assault case using a normative legal research approach. The findings reveal a fragmented regulatory landscape. KUHAP under Law Number 8 of 1981 does not explicitly recognize digital evidence in Article 184 paragraph (1). This normative gap is addressed by UU ITE under Law Number 11 of 2008, which through Article 5 paragraphs (1) and (2) recognizes electronic information and documents as admissible evidence. Constitutional Court Decision Number 20/PUU-XIV/2016 further established that digital evidence must be lawfully obtained during law enforcement proceedings. This framework was subsequently strengthened by the New Criminal Procedure Code under Law Number 20 of 2025, which formally incorporates electronic evidence as a recognized proof category. In the Mario Dandy assault case, digital evidence consisting of video recordings, CCTV footage, and digital communication records was examined through forensic procedures conforming to SNI ISO/IEC 17025-2017 standards. This evidence satisfied both the formal and substantive requirements under UU ITE and proved decisive in establishing the elements of premeditated aggravated assault under Article 355 paragraph (1) in conjunction with Article 55 paragraph (1) of the Criminal Code.